Social Media Brand Communities and Brand Loyalty : An Integrated AHP Approach - Adhikari, Kishalay and Panda, Rajeev Kumar (International Journal of Virtual Communities and Social Networking, 2017)
The dynamic, omnipresent, and frequent on-the-go consumer-brand interactions via social media platforms are significantly changing the branding landscape. A profound comprehension of this change is crucial in assessing brand loyalty. Considering the enormous fame of social media and inherent capabilities of brand communities, the purpose of this paper is to exhibit the contributory role of Social media brand communities (SMBC) towards brand loyalty. A Survey-based empirical study involving young consumers was conducted in the selected cities of Bangalore, Kolkata, and Pune. In contrast to prior works (Algesheimer et al., 2005; Laroche et al., 2012), the authors have incorporated Analytical Hierarchy Process (hereafter AHP) in the study to implement and validate new scales. The outcomes of AHP methodology found shared consciousness and social networking as the most-preferred component and activity respectively. These outcomes would assist brand managers in the optimized allocation of communication budget and formulation of competitive branding strategies to tackle intense competition.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNDAxOC9panZjc24uMjAxNzA0MDEwNA